Thermal insulation of poly(methyl methacrylate) bone cement and hydroxyapatite coatings under induction heating of metal implants - Robert Kamphof; Rob G. H. H. Nelissen; Giuseppe Cama; Bart G. C. W. Pijls (PLoS ONE, 2025)
Prosthetic joint infection after joint arthroplasty has serious consequences for patients. Finding new treatments against prosthesis infection is increasingly urgent due to the growing number of prosthetic joints and increasing prevalence of antimicrobial resistance. This study investigates the feasibility of non-contact induction heating to supplement debridement, antibiotics and implant retention using an implant model. Upper temperature limits for induction heating treatment are established, based on the presence or absence of biomaterials commonly associated with joint replacement implants. Titanium grade 5 coupons were heated using an induction device to 50, 70 and 90°C. Heat transfer through poly(methyl methacrylate) bone cement and hydroxyapatite coatings was studied, with poly(acrylic acid) gel phantoms serving as tissue mimic. Thermal doses delivered at the biomaterial-gel interface were quantified. Thermographic images supported the findings. Thermal doses (CEM43) were calculated to estimate damage to human bone tissue. Safe induction temperatures vary by implant configuration. Cemented implants can be heated up to 70–80°C without risk of mechanical failure or patient harm, depending on the thickness of the cement mantle. For uncemented and hydroxyapatite-coated implants, the temperature limit is 50°C. Since temperatures were measured at the metal-biomaterial interface, higher temperatures could be safe for implant sections farther away from the bone. Thus, non-contact induction heating is a safe treatment strategy for prosthetic joint infection in both modalities.